2019
DOI: 10.24874/ti.2019.41.04.13
|View full text |Cite
|
Sign up to set email alerts
|

Wear Characteristics of Recycled Cast Al-6Si-3Cu Alloys

Abstract: Recycling of Al-Si alloys for high integrity structural components for the automotive industry applications has gained attention in the recent times. In this article, scrap of cylinder heads containing 6.01%Si and 2.62%Cu were recycled by casting into four alloys invariants: base alloy (no alloying elements added), 0.02%Ca, 0.38%Fe and 0.9%Fe+0.45%Mn additions. The structural properties were analysed through optical and SEM/EDS microscopy, X-ray diffraction (XRD). The wear characteristics of the alloys were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These particles were then pulled off from the specimen surface layer due to the repetitive loads. This deepened the shallow grooves to fine grooves revealing a fresh layer of particles, which undergo uniform wear due to stress concentration after heat treatment [35,36]. As the sliding distance increased (1500 m), the wear rate decreased due to the slipping effect produced by the adhesion of specimen surface and undergo plastic deformation, as shown in Fig.…”
Section: Worn Surface Analysismentioning
confidence: 92%
“…These particles were then pulled off from the specimen surface layer due to the repetitive loads. This deepened the shallow grooves to fine grooves revealing a fresh layer of particles, which undergo uniform wear due to stress concentration after heat treatment [35,36]. As the sliding distance increased (1500 m), the wear rate decreased due to the slipping effect produced by the adhesion of specimen surface and undergo plastic deformation, as shown in Fig.…”
Section: Worn Surface Analysismentioning
confidence: 92%
“…To enable the production to be profitable, lower quality input materials are often used today, which, although they have the required chemical composition, may contain a relatively large number of impurities, originating not only from the original input materials, but also from their processing [ 12 , 13 ]. Impurities entering the process during remelting and casting are one of the primary causes of foundry defects and have negative impact on the mechanical properties of casted Al-Si components [ 14 , 15 ]. Solid impurities and various exotic inclusions are one of the primary impurities introduced in the process of implementation of the return material into the melt.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, it was shown that Al-Si alloy-based aviationgrade parts are commonly used while there are fatigue possibilities depending on the 2 working conditions of the aircraft. It is well established that Al-Si alloys are the most important alloys in terms of wear properties and improve with the concentration of Si in the alloys [9]. Wear is one of the most commonly encountered problems in industries, necessitating the replacement of mechanical components that are required but unserviceable.…”
Section: Introductionmentioning
confidence: 99%